2020
DOI: 10.1089/pmr.2020.0051
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Consultation and Effect on Length of Stay in a Tertiary-Level Neurological Intensive Care Unit

Abstract: Background: Patients admitted to an acute care setting with a devastating brain injury are at high risk for morbidity and mortality. These patients and their families can benefit from the psychosocial and decision-making support of a palliative care consultation. Objective: We aim to investigate the characteristics and impact of palliative care consultation for patients under the management of neurosurgical and critical care services with a devastating brain injury in a neurological intensive care unit (ICU) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…From a total of 915 records retrieved, after duplicate exclusion and screening from abstracts, 363 relevant articles were screened from full text; of those, 15 articles [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were adjudicated relevant for inclusion in this review and provided the basis for data and discussion presented on the topic ( Table 1 ). Twelve studies were conducted in a single center, and only three were multicentric studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a total of 915 records retrieved, after duplicate exclusion and screening from abstracts, 363 relevant articles were screened from full text; of those, 15 articles [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were adjudicated relevant for inclusion in this review and provided the basis for data and discussion presented on the topic ( Table 1 ). Twelve studies were conducted in a single center, and only three were multicentric studies.…”
Section: Resultsmentioning
confidence: 99%
“…Such issues may be more easily addressed using formal palliative care consultations. Indeed, a single-center retrospective study conducted in a neuro-ICU found that, in 88% of the cases of palliative care consultations, the need of assistance in defining a patient’s goals of care (88%) [ 19 ] was the main reason of the request. A similar result was reported by Tran et al, who reported “clarifying goals of care” as the main reason for palliative care consultation in 22 patients out of the 25 assessed, as well as other reasons, including assistance in “family support”, “decision making”, “discharge planning” and “communication” [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“… 17 19 Its timely integration is crucial not only for its clinical benefits but also for providing compassionate support to patients and families and aiding in the clarification of care goals. 11 , 12 , 14 , 15 , 23 , 38 To this end, increasing the availability of palliative services for patients with TBI and developing clinical triggers tied to influential drivers of PCC timing could offer a systematic method to enhance consultation processes, moving them upstream to play a preventative role. Beyond standardized triggers, enhancing detection of palliative needs warrants policy efforts expanding access and reducing existing disparities.…”
Section: Discussionmentioning
confidence: 99%
“…10 Timely palliative care consultations (PCCs) have been shown to facilitate decision-making about care goals, reduce hospital stay duration and costs, and minimize non-bene cial interventions without increasing mortality rates in patients with TBI. [11][12][13][14][15][16] Despite these bene ts, integration of palliative care for patients with TBI is limited and varies by sociodemographic and clinical factors, highlighting care discrepancies. 6,[17][18][19][20][21][22] Optimal integration and timing of palliative care in TBI is a crucial yet severely understudied area that needs of further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Having discussions about goals of care and, thus, limitation in invasive measures, ought to occur earlier in a patient's care trajectory (ASCO, 2012). Pottash et al (2020) reported that, in one neurological ICU, for 88% of the cases, the palliative care team was brought in to help define a patient's goals of care. A similar result was reported by Tran et al (2016), who described clarifying goals of care as the main reason for palliative care consultation, followed by providing family support, and assisting with decision-making and communication.…”
Section: How and When The Definition And Discussion Of Goals Of Care ...mentioning
confidence: 99%